2019
DOI: 10.1136/jmedgenet-2019-106072
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a 161-SNP polygenic risk score to family history-based risk prediction: impact on clinical management in non-BRCA1/2breast cancer families

Abstract: BackgroundThe currently known breast cancer-associated single nucleotide polymorphisms (SNPs) are presently not used to guide clinical management. We explored whether a genetic test that incorporates a SNP-based polygenic risk score (PRS) is clinically meaningful in non-BRCA1/2 high-risk breast cancer families.Methods101 non-BRCA1/2 high-risk breast cancer families were included; 323 cases and 262 unaffected female relatives were genotyped. The 161-SNP PRS was calculated and standardised to 327 population cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 31 publications
(26 reference statements)
0
31
0
Order By: Relevance
“…Several studies have examined the effect of PRS on existing risk prediction models, including the Gail Model [39,46,56,[58][59][60][61][62], Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA) [46,63,64], Tyrer-Cuzick (TC) [39,41,46,49,52], BRCAPRO [46], and Breast Cancer Surveillance Consortium (BCSC) [30,40,65] (Table 2). These statistical models utilize a range of well-known breast cancer risk factors such as personal and family history, breast pathology, and lifestyle factors to estimate the risk of breast cancer.…”
Section: Polygenic Risk In Combination With Risk Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the effect of PRS on existing risk prediction models, including the Gail Model [39,46,56,[58][59][60][61][62], Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA) [46,63,64], Tyrer-Cuzick (TC) [39,41,46,49,52], BRCAPRO [46], and Breast Cancer Surveillance Consortium (BCSC) [30,40,65] (Table 2). These statistical models utilize a range of well-known breast cancer risk factors such as personal and family history, breast pathology, and lifestyle factors to estimate the risk of breast cancer.…”
Section: Polygenic Risk In Combination With Risk Prediction Modelsmentioning
confidence: 99%
“…Thus, there is a need to develop new method of risk stratification to inform risk management decisions for women with uninformative results from monogenic testing. Studies assessing the application of polygenic factors for familial cancer have reported that PRS was predictive of breast cancer risk among women from high-risk families with uninformative BRCA1/2 result [7,31,32,34,46,56,64]. Higher PRS has also been reported among women from breast cancer families when compared to those without a family history of the disease [29,31,32], suggesting that breast cancer variants may cluster in affected families.…”
Section: Familial Cancer Clinicmentioning
confidence: 99%
“…Over the past decade our models were built from life course risk factors that include reproductive factors, adiposity at different points in life, age and type of menopause, menopausal hormone therapy, family history of breast cancer, personal history of benign breast disease, and alcohol intake (3)(4)(5)(6). Investigators have added to these models to improve discrimination often measured as the area under the ROC curve (AUC); and include MD (3,(7)(8)(9)(10); endogenous hormones (11); and/or PRS using a variable number of SNPs (12)(13)(14)(15)(16)(17)(18). While combinations of these factors have been evaluated (e.g., lifestyle factors and PRS or lifestyle factors and MD), models that combine measures from all three components (life course risk factors, MD, and PRS) (19)(20)(21) show the highest AUC values at 0.71 (9,22).…”
Section: Introductionmentioning
confidence: 99%
“…46 With regard to the common low-risk variants, our results are consistent with studies which have found that non-BRCA1/2 familial breast cancer cases have a higher PRS than both cases from the general population and cases who carry a BRCA1 or BRCA2 pathogenic variant. [47][48][49][50] Whether the prevalence of rare missense variants in the known breast cancer genes we observed in our families is causally linked to breast cancer, will need very large case-control studies to substantiate further.…”
Section: Discussionmentioning
confidence: 94%